Development of a novel graphene oxide-blended polysulfone mixed matrix membrane with improved hydrophilicity and evaluation of nitrate removal from aqueous solutions. Issue 4 (3rd April 2019) - Rezaee, Reza; Nasseri, Simin; Mahvi, Amir Hossein; Nabizadeh, Ramin; Mousavi, Seyyed Abbas; Maleki, Afshin; Alimohammadi, Mahmood; Jafari, Ali; Hemmati Borji, Saeedeh
Abstract: In this study, four types of mixed matrix membranes were fabricated using polysulfone (as the base polymer) and different contents of graphene oxide (GO) nanosheets (as modifier) through wet phase inversion method. Based on the amounts of GO (0, 0.5, 1, and 2 wt%), the synthesized membranes named as M1, M2, M3, and M4, respectively. The membranes characteristics were evaluated using FE-SEM, FT-IR, and water contact angle measurements. In addition, the performance of the prepared membranes was investigated in terms of basic parameters: filtrate water flux, nitrate removal efficiency, and antifouling properties. Results showed significant improvements of the characteristics of modified membranes with GO. Accordingly, the permeability and hydrophilicity were enhanced and water flux was considerably improved. At operating pressure of 4 bar and nitrate concentration of 110 mg/L, the removal efficiency for unmodified membrane (M1) was 15.5% and for modified M2, M3, and M4 membranes were 22.78%, 39.12%, and 41.37%, respectively. In addition, the results of flux recovery ratio (FRR) showed that the anti-fouling properties of the GO modified membranes were improved due to the increase in membrane surface hydrophilicity.